2018
DOI: 10.1155/2018/1628620
|View full text |Cite
|
Sign up to set email alerts
|

Obesity May Provide Pro-ILC3 Development Inflammatory Environment in Asthmatic Children

Abstract: The prevalence of obesity in children has dramatically increased in the last few decades, and obesity has also emerged as an important risk factor for asthma. Innate mechanisms have been shown to be involved in both diseases, particularly through the recently described innate lymphoid cells (ILCs), in which ILC3s have been linked to obesity both in human and in murine models. The aim of this study was to explore whether being overweight in asthmatic children was associated with elevated circulating ILC3 or ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
(47 reference statements)
1
11
0
Order By: Relevance
“…Besides the here described involvement of cytokines ( Table 1), mucosal immune cells, and bacteria in the ILC3-activating machinery, several other factors have been suggested to be crucial promotors of local ILC3 accumulation and function in humans, such as neurotransmitters, vitamin metabolites, and even lifestyle (e.g., obesity and cigarette smoking) (107,108,193,194). In the case of neurotransmitters, vagus-derived acetylcholin was described to stimulate the PCTR1 pathway in both murine and human ILC3s, favoring the resolution of inflammation (107).…”
Section: Local Regulation Of Human Helper Ilc3smentioning
confidence: 80%
“…Besides the here described involvement of cytokines ( Table 1), mucosal immune cells, and bacteria in the ILC3-activating machinery, several other factors have been suggested to be crucial promotors of local ILC3 accumulation and function in humans, such as neurotransmitters, vitamin metabolites, and even lifestyle (e.g., obesity and cigarette smoking) (107,108,193,194). In the case of neurotransmitters, vagus-derived acetylcholin was described to stimulate the PCTR1 pathway in both murine and human ILC3s, favoring the resolution of inflammation (107).…”
Section: Local Regulation Of Human Helper Ilc3smentioning
confidence: 80%
“…Of interest, several studies have shown a global stimulation of the Th17 response in asthma, with simultaneously increased expression of IL-17 and IL-22 in peripheral mononuclear blood cells (PMBC) and bronchial biopsies from asthmatic patients, this increase being even higher in severe asthmatic patients. Furthermore, increased levels of IL-17 and IL-22 were insensitive to steroids, a characteristic frequently found in patients with neutrophilic airway inflammation and with airway remodeling and specific to severe asthma (25,116,135,136). In a recent work, our group also reported airway remodeling and neutrophilia in a murine model of allergic asthma induced by dog allergen.…”
Section: Involvement Of Il-17 and Il-22 In Asthmamentioning
confidence: 99%
“…The involvement of IL-17 in asthma pathogenesis was further confirmed in murine models, which globally found that ovalbumin sensitization (inhaled, intraperitoneal, or epicutaneous route) followed by inhaled challenge was associated with Th17 response, up-regulation of IL-17 in airways, and that up-regulation of IL-17 enhanced airway neutrophilia and steroid-resistant AHR ( 112 115 ). IL-17 production is also increased in obesity-associated murine models of asthma and asthmatic pediatric patients ( 38 , 39 , 116 ). Data from murine models are summarized in Table 1 .…”
Section: Involvement Of Il-17 and Il-22 In Asthmamentioning
confidence: 99%
“…In addition to Th17 lymphocytes, other cellular sources of IL-17 include invariant NK T cells, gd T cells, cytotoxic T cells, and especially group 3 innate lymphoid cells (ILC3) (71,72). High numbers of ILC3 were found in bronchoalveolar lavage fluid (BALF) from adults with severe asthma, as well as in blood of obese asthmatic children (72,73). Once secreted from Th17 lymphocytes, ILC3 and other cell types, IL-17A and IL-17F induce bronchial epithelial cells and sub-epithelial airway fibroblasts to release potent neutrophil chemoattractants including IL-8 (CXCL8) and CXCL1/GRO-a (74)(75)(76).…”
Section: Pathobiology Of Severe Asthmamentioning
confidence: 99%